The Consolidated asylum and migration acquis : (T. M. C. Asser Press,Cambridge University Press [distributor], 2004)
Probably the best survey and overview to date, The Consolidated Asylum and Migration Acquis contains all the relevant Directives and Regulations on the sensitive and often politicized issues of asylum and migration as adopted by the European Union through 2004. The Directives have been included in a consumer-friendly manner, with an extensive index. Experts, students, parliamentarians, policy makers, the media, lawyers, civil servants and the individuals concerned will easily be able to trace articles and references and their meaning in this Handbook. Europe has been warned by the UNHCR and others that it is coming dangerously close to trespassing upon international minimum norms. This Handbook enables the reader to see clearly where Europe really stands.